Upskilling Guru Kejuruan melalui Pelatihan Kendali Motor Listrik Berbasis Variable Speed Drive - Doni Tri Putra Yanto; Citra Dewi; Dori Yuvenda; Aswardi Aswardi; Rahmat Hidayat; Muslim Muslim; Hermi Zaswita (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research discusses efforts to enhance the professional competence of teachers in Vocational High Schools (SMK) specializing in the field of Electricity. It does so through the implementation of a training program based on Variable Speed Drive (VSD) technology for electric motor control. The training program encompasses two distinct learning approaches: theoretical and practical instruction on motor control using VSD technology. This material forms an essential part of the curriculum for installing electric motors in vocational schools. It is crucial for every teacher to comprehend it thoroughly, as vocational school curricula must adapt to the latest developments in science and technology, commonly referred to as the Fourth Industrial Revolution (Industry 4.0). This research focused on 20 electricity teachers at SMK Negeri 1 Bukittinggi as its subjects. The research findings indicate a significant improvement in teachers' professional competence in electric motor installation, particularly in electric motor control using VSD technology, following the implementation of the training program. This improvement is reflected in the posttest results, with 88.7% of participants passing in this particular subject. In conclusion, the Variable Speed Drive Based Electric Motor Control Training for teachers can effectively enhance their professional competence in electric motor installation, aligning with the demands of Industry 4.0.